Croatian museums and their practice: the present situation - Babić, Darko (muzeolog) (Array, 2009)
From 1991, when it has gained the independence, around the World the Republic of Croatia is foremost identified with the war, the sport and the tourism. The Croatian heritage, especially the museums sector, remained rather unknown. The author presents details about museums in Croatia, theirs activities and on-going new museum projects. A special focus is devoted to The House of Batana, community based museum project as a good example of heritage interpretation practice.